Application Of The Triple Exponential Smoothing Method In Predicting Electronic Equipment Inventory Based On Customer Demand - Lutfil, Muhammad Lutfil Amin Siregar; Samsudin; Triase (Journal of Information Systems and Technology Research, 2023)
PT. Wira Dwika is a company engaged in the production of electronic equipment and product distribution is carried out after the production process takes place. The obstacle that is often faced by companies is the difficulty in determining the number of products that will be provided by the company so that errors often occur in fulfilling customer requests and in predicting supplies for the next period. The system that runs at the company still uses a manual system so that errors often occur in determining the number of products to be distributed, and the Inventory section also often has difficulty determining the stock to be provided in future periods and the demand is more than the number of products already available in production. So it greatly affects profit and loss as well as inventory data processing. So the researchers used the Triple Exponential Smoothing Method to overcome the obstacles faced by the company because the Triple Exponential Smoothing method is an effective method in terms of forecasting. Electronic equipment still uses workbook paper and is less efficient in making product inventory reports. The electronic equipment inventory report input system still uses Microsoft Excel 2007 so that the data obtained is inaccurate and does not yet use electronic equipment inventory storage with a database system, by implementing PHP applications and MySQL databases it can help companies calculate predictions of electronic equipment distribution in the next period. So that it greatly affects profit and loss as well as processing inventory data for electronic equipment still using paper workbooks and is less efficient in making product inventory reports.